Matriciamento e a qualificação de médicos generalistas: um estudo em um município de São Paulo - Garcia, Alessandra Gomes [UNIFESP] (2020)
This investigation derives from upheavals caused by my experience as a public health professional in the city of São Bernardo do Campo, SP. Such city, from 2009 to 2016, has significantly invested in structuring their health service network with plenty of care qualification devices and settings: management collegiate, institutional and matricial support, permanent education areas, among others. The city’s Basic Care follows the Expanded Family Health Strategy (ESF), where, apart from the minimal team with a general practitioner, there are primary care specialists – pediatricians, GPs and gynecologists – whose perspective is the matricial support of the team professionals and especially the general practitioners. This research aimed at analyzing matricial support processes proposed to general practitioners from Expanded Family Health teams in this city. Its specific goals were to map matricial support processes offered to doctors from Expanded Family Health Units; to understand effects of the matricial support processes in clinical practices from the general practitioner’s perspective, discuss and analyze the problematics and potentialities observed by the doctors in order to use this health care model. For this research, qualitative methodology with cartographic inspiration has been used. Dialogue circles with general practitioners from two Basic Health Units (UBS) have taken place, three circles at UBS 01 and two circles at UBS 02. The material collected in the circles has been transcribed after each meeting and has served as a springboard for the following meeting. Besides that, an interview with a manager working in the city within the mentioned period has been conducted and her memories have also composed the produced data. The data production has been constantly crossed by changes in the city, such as the replacements of unit managers, the resignation of general practitioners during the research period. Each material has been analyzed separately and then together, being agglutinated in four axles. The general practitioners who have participated in the research have contributed with relevant memories regarding their professional and educational backgrounds. Apart from that, the work as a general practitioner has been approached, with different perceptions about the technical-relational complexity, mainly facing an assistance model which extrapolates the care actions to a level beyond the programmatic actions. General practitioners are aware of the power of matricial support for the qualification of referrals; expanding solvability and access to care and also learning. However, it has been perceived that hierarchic work relations, fragmented practices, as wellas tensions from divergent ways of considering health care, make matricial support disputable and, therefore, requires work process organization and attention by Management and managers in order to ensure the matricial support processes.